Deep phenotyping of two preclinical mouse models and a cohort of RBM20 mutation carriers reveals no sex-dependent disease severity in RBM20 cardiomyopathy - Lennermann, David; Pepin, Mark; Grosch, Markus; Konrad, Laura; Kemmling, Elena; Hartmann, Joshua; Nolte, Janica L.; Clauder-Muenster, Sandra; Kayvanpour, Elham; Sedaghat-Hamedani, Farbod; Haas, Jan; Meder, Benjamin; et al. (American journal of physiology. Heart and circulatory physiology, 2022)
RBM20 cardiomyopathy is an arrhythmogenic form of dilated cardiomyopathy caused by mutations in the splicing factor RBM20. A recent study found a more severe phenotype in male patients with RBM20 cardiomyopathy patients than in female patients. Here, we aim to determine sex differences in an animal model of RBM20 cardiomyopathy and investigate potential underlying mechanisms. In addition, we aim to determine sex and gender differences in clinical parameters in a novel RBM20 cardiomyopa-thy patient cohort. We characterized an Rbm20 knockout (KO) mouse model, and show that splicing of key RBM20 targets, car-diac function, and arrhythmia susceptibility do not differ between sexes. Next, we performed deep phenotyping of these mice, and show that male and female Rbm20-KO mice possess transcriptomic and phosphoproteomic differences. Hypothesizing that these differences may influence the heart's ability to compensate for stress, we exposed Rbm20-KO mice to acute catecholami-nergic stimulation and again found no functional differences. We also replicate the lack of functional differences in a mouse model with the Rbm20-R636Q mutation. Lastly, we present a patient cohort of 33 RBM20 cardiomyopathy patients and show that these patients do not possess sex and gender differences in disease severity. Current mouse models of RBM20 cardiomy-opathy show more pronounced changes in gene expression and phosphorylation of cardiac proteins in male mice, but no sex differences in cardiac morphology and function. Moreover, other than reported before, male RBM20 cardiomyopathy patients do not present with worse cardiac function in a patient cohort from Germany and the Netherlands.NEW & NOTEWORTHY Optimal management of the cardiac disease is increasingly personalized, partly because of differences in outcomes between sexes. RBM20 cardiomyopathy has been described to be more severe in male patients, and this carries the risk that male patients are more scrutinized in the clinic than female patients. Our findings do not support this observation and suggest that treatment should not differ between male and female RBM20 cardiomyopathy patients, but instead should focus on the underlying disease mechanism.